Intensified decontamination of amoxicillin drug wastewater assisted by liquid-phase micro extraction method. Issue 10 (29th April 2022) - Abbasi, Ali; Rahbar-Kelishami, Ahmad; Seifollahi, Zahra; Ghasemi, Mohammad Javad
ABSTRACT: The presence of pharmaceutical pollutants, including antibiotic contaminants in the environment is one of the most important issues in the world today. We focused on elimination of amoxicillin (AMX) from aqueous media in micro Channel Y-Y shaped. The kinetic studies showed that the reaction kinetic was very fast and extraction equilibrium is attained within 20 s. Key operational parameters such as feed concentration, pH of aqueous solution, and extractant concentration and residence time were optimized. The maximum rate of AMX removal was determined 98.2%. Overall volumetric mass transfer coefficient of amoxicillin k L α, is perused to specify the mass transfer performance. Much higher amoxicillin k L α values acquired in the micro process compare with conventional extraction approved the amoxicillin is easily extracted with a higher ratio at micro-flow. The studies demonstrated that the micro solvent extraction process has considerable potential for environmentally friendly and would be a promising method for wastewater treatment of complex systems. Highlights On-chip liquid-phase microextraction coupled with UV-VIS was introduced. Extraction percentage of 98.2% was obtained using MDEHPA under best conditions. Microfluidic shows the considerable potential for environmentally friendly and amoxicillin removal from aqueous media. GRAPHICAL ABSTRACT: UF0001